Analisis Penggunaan Teknologi Informasi Sebagai Media Pembelajaran Kewirausahaan Terhadap Pemanfaatan Kantin Sekolah Di SMA Muhammadiyah Ambon - Rehalat, Aminah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the relationship between the use of information technology as a medium for learning Social Sciences and the use of the school canteen at SMA Muhammadiyah Ambon. Quantitative methods were used in this research involving surveys and statistical data analysis. The sample for this research consisted of Muhammadiyah Ambon High School students who used information technology as a social studies learning medium and those who did not use information technology. The research instrument is a questionnaire that assesses the level of use of information technology in social studies learning as well as the frequency and type of use of the school canteen. The results of data analysis show that there is a positive relationship between the use of information technology as a social studies learning medium and the use of school canteens, with a high level of significance. The implication of this research is the need to increase the use of information technology in social studies learning to encourage the use of school facilities such as canteens, which can enrich students' learning experiences in the school environment